ANALISIS PENGARUH DIVIDEND PAYOUT RATIO, RETURN ON ASSET, DAN PENJUALAN TERHADAP HARGA SAHAM - Putri, Syarafina; Mukti, Aloysius Harry (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2023)
The aims of this study are to analyze the effect of the Dividend Payout Ratio on stock prices, the effect of Return on Assets on Stock Prices, and the effect of sales on stock prices. This study consisted of 549 samples from sector manufacturing companies listed on the Indonesia Stock Exchange from the 2017-2019 period. The data used in this study is secondary data, the sample was gathered using the purposive sampling method, and the tests were carried out using data regression analysis. The results of this study indicate that the Dividend Payout Ratio variable has a positive significant effect on stock prices, the Return on Asset has a positive significant on Stock Prices, and the Sales variable has a significant positive significant effect on Stock Prices.Keywords: Dividend Payout Ratio, Return on Assets, Sales, Stock Prices.